Linear and Volumetric Analysis of Maxillary Sinus Pneumatization in a Sri Lankan Population Using Cone Beam Computer Tomography. - Hettiarachchi, Pilana Vithanage Kalani Shihanika; Gunathilake, Pulihinga Mudiyanselage Prabhath Chaminda; Jayasinghe, Rasika Manori; Fonseka, Manil Christopher; Bandara, Ranasinghe Mudiyanselage Wikum Roshan; Nanayakkara, Chinthani Deepthi; Jayasinghe, Ruwan Duminda (BioMed Research International, 2021)
Objective. The objectives of this study were to evaluate the linear and volumetric measurements of the maxillary sinus in relation to sex and side on cone beam computer tomographic (CBCT) images in a Sri Lankan population. Methods. A total of 20 sets of CBCT images selected from the database at the Division of Oral Medicine and Radiology, Faculty of Dental Sciences, University of Peradeniya, Sri Lanka, were evaluated. Linear measurements were obtained in a craniocaudal (height), anteroposterior (length), and mediolateral (width) dimensions. Volume was computed by using the same data using a computerized 3D modeling software developed for 3D measurements and calculations. Results. The maximum mean craniocaudal dimension was at the level of the 1st and the 2nd molar tooth bilaterally. The largest average craniocaudal, mediolateral, and anteroposterior extensions of the maxillary sinus using CBCT were 31.71 ± 5.44 mm , 21.28 ± 5.09 mm , and 32.92 ± 4.31 mm , respectively. The differences between the sides and sex showed no statistical significance (P > 0.05), except for the maximum average value in craniocaudal dimension which showed a statistically significant difference in relation to gender (P = 0.02). Conclusion. There is no significant difference in the largest average craniocaudal, mediolateral, and anteroposterior extensions of the maxillary sinus when gender and side were compared. However, the maximum average value in craniocaudal dimension had a statistically significant difference in relation to gender. This study provides valuable knowledge of the anatomical dimensions of the maxillary sinus which may help clinicians in treatment planning.